Success rate of single versus multiple debridement, antibiotics, and implant retention (DAIR) in hip and knee periprosthetic joint infection: a systematic review and meta-analysis - Loay A. Salman (14150322) (2024)
Purpose This systematic review aimed to compare outcomes between multiple and single debridement, antibiotics, and implant retention (DAIR) procedures for early periprosthetic joint infection (PJI) in hip and knee arthroplasty. Methods Four databases were searched from inception till January 2024 for original studies investigating the outcomes of multiple DAIR in hip and knee PJI. The primary outcome was the success rate in eradicating joint infection. This review was conducted per PRISMA guidelines. Results A total of 9 observational studies with 1104 participants were included, with a mean age and BMI of 58.37 years (95%CI: 25.77–90.98) and 31.43 kg/m2 (95%CI: 28.89–34.98), respectively. The mean follow-up period was 58.37 months (95%CI: 25.77–90.98), and the average MINORS score assigned to the review was 17.6 ± 3.46, indicating a low overall risk of bias. An equivalent success rate between single and double DAIR was observed, at 67% (95%CI: 64–71%) and 70% (95%CI: 48–86%), respectively, with no statistically significant difference between the two treatment modalities (p = 0.740). Additionally, the success rate for triple DAIR ranged from 50 to 60%. Conclusion This study suggests that double DAIR is a valid treatment option for acute PJI after TKA and THA, with a success rate comparable to single DAIR (70% vs. 67%, p = 0.740). Triple DAIR achieved success rates ranging from 50 to 60%. However, caution is warranted when interpreting these results due to heterogeneity in host comorbidity factors, DAIR protocols, and antibiotic regimens. Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00590-024-04091-6